2012
DOI: 10.1021/ac301629s
|View full text |Cite
|
Sign up to set email alerts
|

Solution Additives that Desalt Protein Ions in Native Mass Spectrometry

Abstract: The presence of many salts, such as sodium chloride, can adversely affect the performance of native electrospray ionization mass spectrometry for the analysis of proteins and protein complexes by reducing the overall molecular ion abundances and distributing signal for any given charge state into many cationized forms with various numbers of adducts attached. Several solution additives, such as ammonium bromide, ammonium iodide, and NaSbF6, can significantly lower the extent of sodium ion adduction to the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…Ammonium salts have also been used in tissue analysis providing a 5× increase in the total ion current and improvement of signal-to-noise using negative ion MALDI enhancing imaging of glycerophospholipids, sulfatides, and gangliosides [25]. High concentrations of ammonium salts have also been used in ESI for the analysis of protein complexes, preventing protein unfolding and maintaining the complexes intact, allowing so called native MS [26][27][28]. Certain ammonium salts also remove cation adduct formation in ESI [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonium salts have also been used in tissue analysis providing a 5× increase in the total ion current and improvement of signal-to-noise using negative ion MALDI enhancing imaging of glycerophospholipids, sulfatides, and gangliosides [25]. High concentrations of ammonium salts have also been used in ESI for the analysis of protein complexes, preventing protein unfolding and maintaining the complexes intact, allowing so called native MS [26][27][28]. Certain ammonium salts also remove cation adduct formation in ESI [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of ammonium salts have also been used in ESI for the analysis of protein complexes, preventing protein unfolding and maintaining the complexes intact, allowing so called native MS [26][27][28]. Certain ammonium salts also remove cation adduct formation in ESI [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…23 McLuckey and coworkers found that the extent of sodium ion adduction on a protein ion formed by ESI is related to the protein pI, solution pH, and charge state. 18, 26 There is more sodium ion adduction to low charge states, 18, 21, 2527 but there is more adduction of trivalent metal ions to high charge states. 28 …”
Section: Introductionmentioning
confidence: 99%
“…For example, 25 mM ammonium bromide added to an aqueous 1 mM NaCl solution containing ubiquitin decreases the average number of sodium ions adducted to the most abundant charge state of the protein from 6.0 to 0.4 and increases the S/N of this ion by a factor of 66. 25, 27 The ability of different salts to desalt proteins in the ESI droplet is related to the proton affinities of the anions, where anions with low proton affinities lead to less sodium adduction. 27 However, anions with low proton affinities also tend to adduct to the protein as an acid molecule and form ion clusters, 27 which can decrease the protein ion signal.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been developed that enable the presence of mM concentrations of non-volatile salts in nano-ESI analyses. These include adding supercharging reagents [65], additives [66][67][68], or high ammonium acetate concentrations to prevent salt-induced ion suppression/adduction [60,69,70]. More recently it has been shown that using submicrometer nano-ESI capillaries (<0.5 mm compared with conventional emitter sizes of 1-10 lm) enable the detection of well-resolved charge state distributions for native proteins and protein complexes analyzed from highsalt biochemical buffers (e.g.…”
Section: Introductionmentioning
confidence: 99%